Dual Antiplatelet Therapy Plus Argatroban Prevents Early Neurological Deterioration in Branch Atherosclerosis Disease - Xu, Jinghan; Xu, Xuejun; Wang, Huazedan; He, Lanying; Liu, Qiu; Du, Yuejun; Wang, Jian (Stroke (1970), 2022)
[Figure: see text].